Aging and gender constructions from family relationships in the life course - Razo González, Angélica María (2020)
Gender responds to biographies that allow us to observe their identity and determine family relationships and roles learned in different cohorts and vital conditions. Older men and women face situations, generate vital sense, and convey their vision. The purpose of this research was to analyze the construction of gender roles from family relationships during life and their impact on aging. A qualitative phenomenological-hermeneutical methodology and semi-structured interviews were used to analyze how do men visualize feminine and masculine roles and how do women perceive female and male roles. The results showed that the roles defined and transmitted in childhood change along the life course, mostly for experiences and growing old than for ideological change. Building a family is relevant for both sexes, with gender differences. In conclusion, the family builds gender roles as a multifactorial framework; the expectations of mothers and fathers are transmitted with influence of the context and biographical elements. Older men consider the family important as accompany and attention elements, while older women emphasize the emotional importance of the family rather than their instrumental importance.